EXPLORING QRIS ADOPTION AMONG UNIVERSITY STUDENTS USING THE UTAUT MODEL - Shalahuddin, M.; Oktaviyani, Henny; Bella, Cean Maria (Journal of Social and Economics Research, 2025)
Digital transformation in the financial sector has encouraged the use of non-cash payment systems, one of which is the Quick Response Indonesian Standard (QRIS) issued by Bank Indonesia. Students, as digital natives, are seen as one of the segments with the potential to drive this change. This study aims to analyze the intention to use QRIS among students at Sriwijaya University using the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Data was collected through an online questionnaire distributed to 240 respondents, and the analysis technique used was Structural Equation Modeling - Partial Least Squares (SEM-PLS). The results indicate that Performance Expectancy (PE), Social Influence (SI), and Facilitating Conditions (FC) significantly influence Behavioral Intention (BI), while Effort Expectancy (EE) does not have a significant influence. The results also conclude that Facilitating Conditions (FC) and Behavioral Intention (BI) influence Usage Behavior (UB). The findings provide insights into the factors that partially influence the intention to use QRIS and how to develop strategies to encourage QRIS usage among the younger generation.